2018
DOI: 10.24200/sci.2018.20325
|View full text |Cite
|
Sign up to set email alerts
|

Lean design management using a gamified system

Abstract: Design process, due to its information-and innovation-intensive nature, is highly susceptible to change and thus, waste. This attracted the attention of lean design/construction professionals in the past few years. However, limited, if any, researches have addressed this issue from the human behavior perspective. This research proposes a method that exploits the potential of the Last Planner ® System (LPS) in design management. The main contribution of this paper is improving the applicability of the LPS to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Five results are common to the two studies [5,[48][49][50][51]. Also, there is an increase from two to four case studies of gamification in the construction industry [5,6,38,41], which is one of the focuses of this research.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Five results are common to the two studies [5,[48][49][50][51]. Also, there is an increase from two to four case studies of gamification in the construction industry [5,6,38,41], which is one of the focuses of this research.…”
Section: Resultsmentioning
confidence: 90%
“…In this Systematic Literature Review, 23 articles were analyzed [5,6,15,17,[23][24][25][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Since gamification is a multidisciplinary approach, the database search results show a growth in publications on the topic in all fields of study.…”
Section: Resultsmentioning
confidence: 99%
“…This led to increases in cooperation and task completion at the individual and organizational levels (Yilmaz & O'Connor, 2016). Similarly, Khanzadi et al (2018) tested the effects of a gamified pay-for-performance system for lean design management of construction teams and found that gamification effectively enhanced team efficiency by removing the non-value-adding tasks from the design processes and motivating design engineers.…”
Section: Gamification For Task Performancementioning
confidence: 99%
“…Multiple studies have shown that gamification supported desired outcomes such as employee learning (Brull et al, 2017), employee well-being (Dadaczynski et al, 2017), and employee engagement (*Hussain et al, 2018; *Silva et al, 2019). Similarly, several studies have demonstrated that gamification reduced unwanted outcomes, such as eliminating non–value-adding tasks (Khanzadi et al, 2018) and reducing stress levels when embedded in a workplace wellness program (Lowensteyn et al, 2019). For gamification to be effective in workplace applications, however, autonomy (Mitchell et al, 2020) and ease of use (Georgiou & Nikolaou, 2020) are crucial to successful implementation.…”
mentioning
confidence: 99%
“…Some works did not propose a game, however, they contained ideas related to gamification [55,56]. In [55] a generic gamification enterprise platform was proposed that consisted of rules authored using a business rule management system.…”
Section: Gwap Gamification and Serious Gamesmentioning
confidence: 99%